Pengaruh Rasio Kecukupan Modal (CAR) Dan Pembiayaan Tidak Lancar (NPF) Terhadap Profitabilitas Pada Bank Umum Syariah di Indonesia Periode Tahun 2019-2023 - Chamariyah Chamariyah; Subijanto Subijanto; Imroatul Firdausiyah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This type of research is quantitative research. The approach used is an explanatory approach. The sample used was 45 Financial Reports of Islamic Commercial Banks in Indonesia registered with the OJK in 2019-2023. The analysis tool uses SmartPLS (Partial Least Square). The purpose of this study, 1) to test and prove the direct influence of the Capital Adequacy Ratio (CAR) on the profitability of Indonesian Islamic Commercial Banks. 2)To test and prove the direct influence of Non Performing Finance (NPF) on the Financing of Indonesian Islamic Commercial Banks.The results of this study indicate that: 1) Capital Adequacy Ratio has a significant positive effect on Profitability in Islamic Commercial Banks for the 2019-2023 period. 2) Non Performing Finance (NPF) has a significant effect on profitability.